Implementation of a Wide-Area Monitoring and Fire Warning Model Using Lora Mesh - Đặng Phước Hải Trang; Nguyễn Tài Tiệp; Phan Công Danh; Nguyễn Nhật Hiên; Ngô Đình Thanh; Phạm Văn Khoa (Journal of Technical Education Science, 2025)
LoRa technology facilitates intelligent IoT solutions that address some of the most significant issues confronting our world: the management of energy, the reduction of natural resources, the control of pollution, and the efficiency of infrastructure. This study has comprehensively constructed a LoRa network model consisting of one master device and four slave devices that perform environmental parameter sensing and fire alerting based on basic factors such as temperature, humidity, gas concentration, and fire source. Based on LoRa wireless communication technology, the study has built a network for transmitting information between multiple data collection points placed at distant locations using the LoRa E32 design. A visual interface on a web platform has been constructed so that the parameters at the measurement points can be remotely monitored. Experimental results show that the model operates stably in a real environment. In addition, the evaluation of power consumption at the measurement points with different operating modes also indicates that the model can operate stably and consume low power over a long period of time with a battery power source.